2016
DOI: 10.1086/688516
|View full text |Cite
|
Sign up to set email alerts
|

Hemodynamic Evidence of Vascular Remodeling in Combined Post‐ and Precapillary Pulmonary Hypertension

Abstract: Although commonly encountered, patients with combined postcapillary and precapillary pulmonary hypertension (Cpc-PH) have poorly understood pulmonary vascular properties. The product of pulmonary vascular resistance and compliance, resistance-compliance (RC) time, is a measure of pulmonary vascular physiology. While RC time is lower in postcapillary PH than in precapillary PH, the RC time in Cpc-PH and the effect of pulmonary wedge pressure (PWP) on RC time are unknown. We tested the hypothesis that Cpc-PH has… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
59
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 39 publications
(69 citation statements)
references
References 54 publications
10
59
0
Order By: Relevance
“…However, we also included subjects who underwent echocardiography within 2 days after RHC, which somewhat mitigates indication bias. We are unable to manually review the RHC tracings for the accuracy of the computer‐generated pressure values, although we have previously reported that this difference is likely to be small in our population 10. A small minority of TTE studies performed at our institution are “limited” studies in which a full interrogation of the TRV may not have been attempted.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…However, we also included subjects who underwent echocardiography within 2 days after RHC, which somewhat mitigates indication bias. We are unable to manually review the RHC tracings for the accuracy of the computer‐generated pressure values, although we have previously reported that this difference is likely to be small in our population 10. A small minority of TTE studies performed at our institution are “limited” studies in which a full interrogation of the TRV may not have been attempted.…”
Section: Discussionmentioning
confidence: 94%
“…We extracted clinical and hemodynamic data from all adult patients undergoing RHC at Vanderbilt between 1998 and 2014. The method of data extraction has been described in detail elsewhere 9, 10, 11. We included only subjects who underwent a TTE within 2 calendar days before or after RHC.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…35 In another larger scale study, fluid challenge did not affect the time constant of the pulmonary circulation, or PVR×C PA , in Cpc-PH or in PAH, while it decreased it significantly in Ipc-PH, suggesting fixed pulmonary vascular remodeling in Cpc-PH. 36 Biological support for a Cpc-PH phenotype was recently provided by an analysis of a large database of 2817 PH patients from Vanderbilt University in Nashville. 37 In that study, patients with Cpc-PH were younger but with more severe pulmonary vascular disease than patients with Ipc-PH, despite similar comorbidities and prevalence, severity, and chronicity of LHD, and presented with 75 exonic single-nucleotide polymorphisms enriched in pathways involving cell structure, extracellular matrix, and immune function that were shared with PAH and not with Ipc-PH patients.…”
Section: The Diastolic Pulmonary Pressure Gradientmentioning
confidence: 99%
“…We recently showed that pulmonary vascular physiology in Cpc-PH, as measured by the resistance-compliance relationship, resembles PAH more than Ipc-PH, suggesting a potential shared etiology (11). Although prior papers have provided valuable information (2,3,5,1216), our understanding of Cpc-PH etiology and pathophysiology is limited, as no biological data have been reported in this population (17).…”
Section: Introductionmentioning
confidence: 99%